Conflict Management Styles of Educational Managers in Selected Higher Educational Institution in Sulu: Vis-à-vis Teaching Performance - Aurizia Siraji (Philippine Association of Institutions for Research, Inc., 2019)
Conflict is inevitable in life and the challenge is how leaders can precisely manage it. In this respect, for pragmatic and academic purposes and to provide useful information on conflict management styles for the harmonious and globalized working environment this study determined the appropriate conflict management styles to address specific organizational related conflicts in HEIs of Sulu. To obtain the needed data, the researcher employed the purposive random sampling method, using twenty-five (25) educational managers in Higher Educational Institutions (HEIs) of Sulu includes 230 faculty members to determine the most common organizational-related conflict and the most effective management styles. Employed descriptive- survey method 0.192 is greater than 0.05 confidence levels that provide evidence to say conflict management styles of educational managers are not significant predictor to the teaching performance of the faculty in HEIs. Educational managers in HEIs should initiate an action plan to improve the programs of managing conflict to approximately make these styles uniform in HEIs being the people belong to common tribe and lifestyles. Moreover, mentoring the workers through the experience managers should be encouraged at the workplace. Finally, the study on conflict is highly recommended to scrutinize the effect on the faculty.